Teachers Digital Identity Management towards Their Current e-Professionalism: A Case in Indonesian EFL Context - Supriadi, Yadi; Pujasari, Ratu Sarah; Ruslan, Ruslan (Universitas Siliwangi, 2022)
This study aims to investigate how teachers portray their digital identity towards their professionalism as a teacher which is manifested online. This descriptive case study involved four participants who were in-service English teachers from four schools in Tasikmalaya, West Java, Indonesia. The data were collected by conducting a semi-structured interview, after that, the data were analyzed by using Thematic Analysis (TA) based on Braun and Clarke framework analysis. Based on the results of the analysis, this case study produced three general aspects, namely social media preferences, teachers' participation in professional development, and teachers' unfamiliarity with digital identity. The findings of this study explain how English teachers describe their digital identity towards their current e-professionalism. Therefore, the results of this study provide empirical evidence and become a reference for other English teachers about the benefits of digital identity management that will help them improve their professional reputation in an online setting. Keywords: Digital literacy; digital identity; e-professionalism; online identity; teacher’s e-professionalism.